2014
DOI: 10.1590/1806-9282.60.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection and gastrointestinal symptoms on Chilean pregnant women

Abstract: Objective: the aim of this research was to determine the prevalence of Helicobacter pylori infection on Chilean pregnant women and its relationship with the appearance and severity of hyperemesis and dyspepsia. Methods: quantitative study of prevalence in a transversal cut with variable analysis. The sample was taken from 274 Chilean pregnant women from the Bío Bío province through vein puncture between June and December, 2005. Pregnant women were informed of this study, interviewed and signed an informed cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 9 publications
(14 reference statements)
0
22
1
2
Order By: Relevance
“…The diagnosis of H. pylori according to the laboratory findings contained serology, urea breath test, stool antigen or polymerase chain reaction (PCR) (8,9).…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of H. pylori according to the laboratory findings contained serology, urea breath test, stool antigen or polymerase chain reaction (PCR) (8,9).…”
Section: Definitionsmentioning
confidence: 99%
“…The prevalence of this infection is related to economic and social factors, including income level and living conditions during childhood, poor hygiene, and overcrowding (8,9). H. pylori prevalence during pregnancy is vary widely between different geographical regions (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperemesis gravidarum [8][9][10][11][12] Preeclampsia [13][14][15]23] Iron-deficiency Anemia [16][17][18][19] Intrauterine growth Restriction [20][21][22]27] Spontaneous abortion [24][25][26] and inflammatory damage over the gastric epithelium resulting in gastrointestinal disturbance such as hyperemesis gravidarum. H. pylori sequesters essential micronutrients from the host organism such as Iron (Fe) and it causes iron deficiency anemia.…”
Section: Referencementioning
confidence: 99%
“…Güngören et al [10] carried out a study with pregnant women with HG symptoms; they divided them into three categories, mild, moderate and severe ones; a higher positivity rate of H. pylori´s DNA by means of PCR was found in 21 pregnant women that corresponded to 87.5% of the severe category group (p=0.001). They concluded that there was a positive correlation between H. pylori infection and HG.…”
Section: Hyperemesis Gravidarum (Hg)mentioning
confidence: 99%
“…The exemplary onset is inter alia 4 -8 weeks and persist to 16-18 weeks of gestation. Vomiting and nausea in pregnancy named emesis gravidarum (8,10) . The reasons for queasiness and vomiting in pregnant remain obscure, so various conceivable causes have been researched (11) .…”
Section: Introductionmentioning
confidence: 99%